REMEMBRANCE AS A MEANS OF INCREASING THE SPIRITUAL ABILITY OF SURAU ASRAFUL AMIN CONGREGATION KEC. STABAT KAB. LANGKAT - Syarifuddin Syarifuddin (Proceeding International Seminar of Islamic Studies, 2023)
Efforts to improve the spiritual ability of the community in accordance with Islamic religious teachings still need attention, especially from academic circles. This is because of the weak spiritual consciousness of people today who are now experiencing a new order that is always rapidly changing. Providing and improving spiritual values in students and students is one of the important researches carried out, because this spiritual ability is able to reduce the ability of the intellect if in carrying out the life of this intelligent mind is tested with life problems. The role of remembrance as spiritual education becomes increasingly important when many people are affected by the busy mapping of the world which is now rapidly changing so that very little spiritual knowledge is obtained from parents, neighbors, or study institutions. Places of recitation, mosques and especially surau have begun to empty. Religious leaders and ustad and ustajah have done a lot of motivation in the form of studies to the people but have not positioned a significant situation. Therefore, the author tries to highlight by practicing dhikr through surau and mosques as a means of spiritual enlightenment.The activity of Remembrance is doing the work of remembering Allah and forgetting anything other than Allah when in remembrance. So the implications of such remembrance include remembering, paying attention, and feeling that he is always being watched by God and even has a broad influence on the soul and consciousness which is then actualized in patterns of thought and behavior. And it can be said that dhikr is a spiritual consciousness in the soul that is integrated with the Islamic way of thinking and acting according to Islamic Shari'a, whether someone is standing, sitting, lying down, or not. This awareness is central to every action of a Muslim.